2014
DOI: 10.4028/www.scientific.net/amr.941-944.895
|View full text |Cite
|
Sign up to set email alerts
|

The "Comfort in all Respects" Principle Implementation by the Example of an Elementary School

Abstract: The modern materials and technologies have an ability to provide a solution of the main goal of modern construction − maximum comfort. This article shows the implementation of comfortable building in a project of primary school. All the components of comfort have been taken under consideration: a rational space-planning, energy efficiency, acoustic isolation, air-tightness, daylight, fire safety, visual aesthetics. Special attention has been given to energy-efficiency: heat transfer coefficients have been calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Authors of the thesis [2] claim that nevertheless "even with a growth of average security with housing, the share of the people having housing of "low" quality doesn't decrease". Really, such problem has a wide circulation in the territory of St. Petersburg, but by sight authors of this article can be found the ways allowing "to go to a meeting" to the population, having reduced housing cost, for example, by means of cooperation of government bodies and commercial banks to present the most favorable conditions for receiving a mortgage in the new building, for example, to young families [6][7][8][9].…”
Section: Sequence Of Implementation Of Renovationmentioning
confidence: 99%
“…Authors of the thesis [2] claim that nevertheless "even with a growth of average security with housing, the share of the people having housing of "low" quality doesn't decrease". Really, such problem has a wide circulation in the territory of St. Petersburg, but by sight authors of this article can be found the ways allowing "to go to a meeting" to the population, having reduced housing cost, for example, by means of cooperation of government bodies and commercial banks to present the most favorable conditions for receiving a mortgage in the new building, for example, to young families [6][7][8][9].…”
Section: Sequence Of Implementation Of Renovationmentioning
confidence: 99%
“…In the actual values of the resistances to heat transfer may not coincide with the calculated. It affects the parameters of the energy efficiency of buildings [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The higher the thermal shielding level of building envelopes the smaller is the heat loss through the building envelope [2]. Many scientists worked on this issue [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%